Re-thinking sorghum crop as a relevant component of crop rotations in US Great Plains - Marziotte Bartaburu, Lucia (Kansas State University, 2024)
Grain sorghum (Sorghum bicolor L. Moench) is a major cereal crop in the United States (U.S.), especially within the “Sorghum belt”, in the central US Great Plains region. This study explores the potential for sorghum crop to fit in more intensified crop rotations, with the strategy of shortening the duration of the crop growth cycle and evaluating the opportunity of including a follow up winter cereal in the cropping sequence. The overall outcomes of this project can help to offset the decline in cultivated area experienced during the last decades and promote more investments in crop improvement focusing on short-cycle hybrids for intensifying current agricultural farming systems. More specifically, this study evaluates the adoption of early maturing sorghum hybrids as a strategy to intensify the cropping sequence, suggesting that such hybrids could maintain yields (or have a minor yield reduction) with fewer leaves, tested via integration of field data with a crop growth simulation model (Agricultural Production Systems Simulator, APSIM). Chapter 2 assesses the impact of leaf removal after flowering time on sorghum yields through in-silico analyses and field data, evaluating different commercially available sorghum hybrids with different number of leaves, and varying crop growth cycle. Field experiments to evaluate the hypotheses from chapter 2 were divided into two, the first set was executed using four historical sorghum hybrids with field studies conducted during 9 years (2015-2023). The second set of field experiments consisted of testing 20 modern commercially available sorghum hybrids, during 2022 and 2023 growing seasons. The main outcome across studies is the lack of a significant decrease in sorghum yield when leaf removal was beyond four leaves after flowering time and with negligible yield differences between hybrids with 15 to 21 leaves and 90 to 112 days to maturity. Chapter 3 explores the economic viability and environmental implications of a sorghum-wheat cropping system versus wheat- or sorghum- monocrop, using spatial analysis to identify Kansas regions most beneficial for these alternative cropping scenarios. This study documented three well-defined areas, two favorable for the sorghum-wheat rotation obtaining better profits and one for wheat monocrop as the most profitable option. These findings underscore the importance of including and enhancing the productivity of early-maturing sorghum hybrids in crop improvement programs with the goal of intensifying our current agricultural systems in the central US Grain Plains region. The economic analysis reveals that sorghum-wheat rotation can offer superior profit margins over monocropping in most of Kansas, providing a guide for farmers to optimize land use efficiency and profits over time. This dissertation contributes to the discourse on sustainable agricultural practices by promoting adaptive breeding strategies and rotational systems to navigate the complexities of modern agriculture, stressing the need for improving diversification and intensification of our current farming systems.
Keywords: APSIM; Defoliation; Economics; Cycle length